The Influence of School Principals' Digital Leadership and Teacher Self-Efficacy on Teacher Technology Use - Ikhwan, Muh. Saidil; Andriani, Dwi Esti (Tarbawi : Jurnal Ilmu Pendidikan, 2024)
The purpose of the study was to see how the effect of digital leadership and teacher self-efficacy on teacher technology use. The study used a quantitative approach. The study began in March-May 2024. This study used a simple random sampling technique. The sample of this study was 169 teachers. The study was conducted in high schools in Sleman Regency, Yogyakarta. Data analysis used simple linear regression and multiple linear regression. Data collection techniques used questionnaires and documentation. The results of the study were that digital leadership had an impact on teacher technology use by an R2 value of 0.046, teacher self-efficacy influenced teacher technology use by an R2 value of 0.030, and together digital leadership and teacher self-efficacy influenced teacher technology use by an R2 value of 0.118. . Future researchers can conduct research by considering other variables that can influence technology use.